Effectiveness of Neighborhood Watch Programs in Reducing Burglary Rates in Urban Areas - Ade Wulan Ramdani (Mahogany Journal De Social, 2024)
The aim of this study is to assess the effectiveness of Neighborhood Watch Programs (NWPs) in burglary prevention in urban neighborhoods by filling some of the gaps in the literature by using a quasi-experimental research design and strong statistical methods. Data sources: police records, community surveys and interviews samples from neighbourhoods with and without NWPs Descriptive statistics showed significantly reduced burglary rates in NWP areas (M = 4.5) compared with non-NWP areas (M = 7.3) with a statistically significant difference (t = -5.32, p < .001, respectively). Further ANOVA, ANCOVA and multiple regression analyses confirmed that NWPs have a significant effect on burglary reduction, independent of property socioeconomic status or police presence. Furthermore, a significant negative correlation was found between community involvement and burglary rate (r=-0.67, p<0.001), thus reaffirming the strong relevance of community involvement in the crime prevention context. These findings support the strong deterrent effect of NWPs on burglary and hold important implications for policy makers and law enforcement. The promotion and facilitation of NWPs is a potential key intervention in urban crime prevention and future research should test their effectiveness with regards to broader crime categories and program level outcomes.